After obstetric fistula repair; willingness of women in Northern Nigeria to use family planning (2018)
Utilisation of modern family planning (FP) is important for women with obstetric fistula (OF). Preventing pregnancy ensures a proper healing and the success of fistula repair. In Northern Nigeria, prevalence of OF is high while the prevalence of FP utilisation is low. This study assessed the willingness to use family planning among 420 women receiving care at obstetric fistula centres in three northern Nigerian States using a semi-structured questionnaire. Concerning family planning methods, 56.7% were aware, only three (1.3%) had ever utilised any method and 63.8% were willing to use a family planning method in the near future. Age, type of marriage and the presence of surviving children were the significant predictors of willingness to use family planning among women with fistula. There is a moderate awareness of family planning with very low utilisation rates. However, a high proportion of these women are willing to use FP. Therefore, there is a need for integration of FP services with OF services.